Newly designed flared-end covered versus uncovered self-expandable metallic stents for palliation of malignant colorectal obstruction: a randomized, prospective study - Soo Jung Park; Yehyun Park; Hyun Jung Lee; Jae Jun Park; Jae Hee Cheon; Won Ho Kim; Tae Il Kim (Intestinal Research)
Background/Aims Self-expandable metallic stents (SEMSs) are widely used as palliative or bridge to surgery treatments in patients with malignant colorectal obstruction (MCO). Stent occlusion is more common with uncovered stents, but stent migration is more common with covered stents. Our purpose was to compare the efficacy and safety of a newly designed covered SEMS with an uncovered proximal flared end (CSEMS-UPF) with that of the conventional uncovered SEMS (UCSEMS) in the treatment of MCO. Methods This prospective randomized trial was conducted at a tertiary-care academic hospital. We enrolled 87 patients with stage 4 cancer and MCO: colorectal cancer in 60 patients and extracolonic cancer in 27 patients. Insertion of UCSEMS was randomly assigned to 43 patients, and 44 patients received the CSEMS-UPF. The primary outcome was the duration of stent patency after successful placement. The secondary outcomes were the number of patients with technical and clinical success and early and late complications from the stent insertion. Results The median patency of the stent did not differ between the UCSEMS and CSEMS-UPF groups (484 [231–737] days vs. 216 [66–366] days, P = 0.242). The technical and clinical success rates did not differ significantly between the groups, either (100.0% vs. 93.2%, respectively, P = 0.241; 100.0% vs. 92.7%, respectively, P = 0.112), nor did the early (n = 2 [4.7%] vs. n = 4 [9.8%], P > 0.999) or late (n = 12 [27.9%] vs. n = 15 [36.6%], P > 0.999) stent complication rates differ between the groups. Conclusions The UCSEMS and newly developed CSEMS-UPF are similarly effective treatments for MCO, with no differences in the stent migration or occlusion rates (Clinical trial registration number: NCT02640781).